Robot Corruption-Detector: Media Pembelajaran Antikorupsi untuk Anak - Sari, Ratna Candra; Fauziah, Puji Yanti; Ilyana, Sariyatul; Kurniawan, Erry Eka (Integritas : Jurnal Antikorupsi, 2020)
This study aims to develop an anti-corruption learning media called "Corruption-Detector" Robot and to test its effectiveness in improving the understanding of anti-corruption values. Research and development was implemented by using ADDIE development procedure (Analyze, Design, Develop, Implementation, and Evaluation). (1) Analyze is the process of determining learning goals, identifying children's needs, and determining the appropriate learning media; (2) Design is the process of designing learning media; (3) Develop is validating the learning media; (4) Implementation is a trial of learning media on children; and (5) Evaluation is carried out to analyze the suitability of product to the needs of children and to improve its quality. An experiment was used to test the effectiveness of the learning media. The subject of implementation was students of Bee Smart Al Hafidz Kindergarten Yogyakarta. The results of the study show a significant increase of knowledge on the understanding aspect about honesty and attitude that should be imitated. Although increased understanding of the effects of dishonest is not significant, but it has a fairly strong effect-size.